Occupational Safety And Health System For Radiation Workers In The Conventional Radiology Room Rumkit Tk II Pelamonia Makassar - A. AR. Rakhmansya Iskandar; Muh. Rusli; Cisya Fadhilah Nur Sadiyyah (Lembaga Pengembangan Kinerja Dosen, 2023)
K3 system for radiation workers in the conventional radiology room at TK II Pelamonia Makassar. The aim of this research is to determine the completeness and compliance of radiation workers in implementing K3. The K3 system in the Conventional Radiology Room at Tk II Pelamonia Makassar is to use PPE aprons when the radiation is carried out. The PPE apron is used only if the patient requires assistance during the radiation. Radiographers also carry out occupational safety and health training and carry out routine health checks carried out by hospitals. When the radiation is carried out, the radiographer stands behind a wall/screen coated with Pb. Radiographers also always use TLD when on duty or carrying out radiation.